Resource Conservation Technologies for sustainable agriculture - Kaur, Ramanjit; Singh, Avtar (Indian Farming, 2015)
Resource Conservation Technologies (RCTs) is the practice which result in improvement of efficiency use of the natural resources. RCTs range from simple surface seeding, where wheat seed is broadcast on the non-ploughed soil; no till with a special opener for placing seed in the no tilled soil; reduced tillage and bed planting.